Diagnostic value of serial measurement of C-reactive protein in serum and matrix metalloproteinase-9 in drainage fluid in the detection of infectious complications and anastomotic leakage in patients with colorectal resection - Kostić, Zoran; Panišić, Marina; Milev, Boško; Mijušković, Zoran; Slavković, Damjan; Ignjatović, Mile (Vojnosanitetski pregled, 2015)
Background/Aim. Postoperative infectious complications are one of the most important problems in surgical treatment of colorectal cancer (CRC), being present in up to 40% of patients. The aim of this paper was to establish the significance of serial measurement of C-reactive protein (CRP) in serum and matrix metalloproteinase-9 (MMP-9) in drainage fluid for the detection of infectious complications and anastomotic leakage (AL) in patients with colorectal resection. Methods. CRP and MMP-9 values in serum and drainage fluid, respectively, were measured on the first, third, fifth, and seventh postoperative day (POD) in 150 patients with colorectal resection and primary anastomosis. The values obtained were compared between the patients without complicatons and those with surgical site and remote infections and AL. Results. Surgical site infections (SSIs) were observed in 41 (27.3%), and remote infections in 10 (6.7%) patients. Clinically evident AL was observed in 15 (10%) patients. In 82% of the patients with SSIs, serum CRP value on POD 5 exceeded 82 mg/L, with 81% specificity. AL was reported in 85% and 92% of the patients on PODs 5 and 7, respectively, with CRP values of 77 mg/L and 90 mg/L, respectively. The specificity was 77% for POD 5 and 88% for POD 7. All the patients with CRP values exceeding 139 mg/L on POD 5 had some of SSIs and/or AL. The mean values of MMP-9 were not statistically different between the group without complications (n = 99) and the group with AL (n = 15). Conclusion. Serial measurement of CRP is recommended for screening of infectious complications of colorectal resection. Patients with CRP values above 139 mg/L on POD 5 cannot be discharged from hospital, and require an intensive search for infectious complications, particularly AL. MMP-9 measurement in drainage fluid is not relevant in the detection of AL in patients with colorectal resection.